Acupotomy for Superior Cluneal Nerve Entrapment Syndrome: A Review of Randomized Controlled Trials - Hye Min Kim; Jae Soo Kim; Hyun Jong Lee; Jung Hee Lee; Sung Chul Lim; Yun Kyu Lee (Journal of Acupuncture Research, 2024)
This review aims to analyze the efficacy of acupotomy in treating superior cluneal nerve entrapment syndrome (SCNES) by summarizing the findings of randomized controlled trials (RCTs). The RCTs were retrieved from seven databases (i.e., the Cochrane Library, PubMed, Embase, China National Knowledge Infrastructure, Korean Studies Information Service System, Research Information Service System, and Oriental Medicine Advanced Searching Integrated System). Seven RCTs were selected for this review. The results indicate that acupotomy is promising for providing significant pain relief and improving function in patients with SCNES. However, more high-quality RCTs are required to establish the long-term effectiveness and safety of acupotomy. This review provides valuable insights for clinicians and researchers in the management of SCNES.